Biomimetic Composite Scaffolds to Manipulate Stem Cells for Aiding Rheumatoid Arthritis Management. (28th May 2019) - Zhao, Yue; Wang, Zhonghan; Jiang, Yingnan; Liu, Hou; Song, Shanliang; Wang, Chenyu; Li, Zuhao; Yang, Zhe; Liu, He; Wang, Jincheng; Yang, Bai; Lin, Quan
Abstract: Stem cell transplantation is a promising alternative therapy for rheumatoid arthritis (RA) patients, with the potential to suppress autoimmune inﬂammation and prevent joint damage. However, widespread application of RA therapy based on stem cell transplantation is limited due to poor migration, local retention, and uncontrolled differentiation of stem cells. Here, inspired by the dynamic construction of bone matrix, a structurally and functionally optimized scaffold for loading bone marrow stem cells (BMSCs) is designed to aid RA management. The composite scaffolds consist of stiff 3D printing porous metal scaffolds (3DPMS) and soft multifunctional polysaccharide hydrogels, wherein 3DPMS meet the requirements for large‐scale bone defects caused by RA. Attractively, the fabricated hydrogels on the composite scaffold are self‐healable, injectable, biocompatible, and biodegradable, which endow the resultant scaffold many aspects mimicking the extracellular matrix (ECM). After encapsulation of BMSCs, hydrogels are administered into the inner pores of 3DPMS, abbreviated as BMSCs@3DPMS/hydrogels. In this study, BMSCs@3DPMS/hydrogels have a good effect on improving RA, such as remodeling of knee joint articular cartilage, inhibition of inﬂammatory cytokines, and promotion of subchondral bone regeneration. Besides RA, the innovative scaffolds may also serve as an ideal biomaterial for other bone regenerative therapies in various orthopedic diseases. Abstract : A new scaffold to manipulate stem cells is developed for aiding rheumatoid arthritis management. The scaffold is prepared by combining multifunctional hydrogels with 3D printing metal scaffolds. After loading stem cells, the composite scaffold can significantly inhibit inflammatory factors, rebuild damaged cartilage, and promote the formation of subchondral bone, thereby exhibiting excellent performance in treating rheumatoid arthritis.